Enhanced robotic application with topology formation for secondary school RBT course - Tan, Kai Ying (2020)
This project develops a simple, cheap and accessible robotic application with additional formation topology for secondary school RBT course. It will provide an affordable robotic platform built using low cost components so that it can be purchased in large quantities by secondary school. Suitable robotic application according to the RBT course syllabus will be made possible for students to learn with minimal effort. An additional formation topology is added to facilitate students’ learning and make the learning process become more interesting. Although there are many different kinds of robotic application available on the market with various functionalities such as linefollowing function and obstacle-avoidance function, each of them still exists with some limitation, in which they are costly and secondary school cannot afford to purchase in large quantities. The application developed in this project is multiple robotic cars built using ESP8266 microchip as the main component. ESP8266 microchip is equipped with low cost Wi-Fi feature for easy access to the Internet and highly-integrated onchip features that offers reliability, compactness and robustness. ESP8266 microchip is also equipped with Wi-Fi server and Wi-Fi client that allow server-client communication for movable group of mobile devices. The open source Arduino IDE is used as the software framework in this project. For smart obstacle avoidance, ultrasonic sensor modelled HC-SR04 is used to measure the distance of the obstacle, alongside with a buzzer to alert if the robotic car is approaching an obstacle. In the aspect of automatic lighting control, LDR sensor is used to measure the brightness of the room, and LED is used as the headlight of the car, which will turn on when it is dark and off when it is bright. A mobile application using online open source MIT App Inventor 2 is developed to control the motion for the master of the robotic car. While the master robotic car controls the motion of the subsequent robotic car through Wi-Fi server and Wi-Fi client features built in ESP8266 microchip. The project result shows the master robotic car is able to perform functions according to the commands from mobile application which is to move back and forth, turn left and right, while the subsequent robotic car is able to follow the commands sent by the master. The robotic car is able to detect obstacle, room brightness and react to the situations automatically. The end product is later tested for its speed in movements and the accuracy to detect obstacle and room brightness.